Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12888-021-03254-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of coping styles and psychological distress among patients with insomnia disorder

Abstract: Background Insomnia appears to be one of the most frequent sleep complaints in the general population. It has significant negative impact on daily functioning. However, there has been little research that described the effect of coping style in insomnia disorder. Methods The Simplified Coping Style Questionnaire (SCSQ) was used to evaluate 79 adult patients with insomnia disorder alongside 80 healthy controls. Additionally, sleep quality was assess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…Specifically, active coping was adversely associated with poor sleep quality, whereas negative coping was positively related to it. Similar results were also found in previous studies [ 17 , 33 ]. The underlying mechanism might be that passive coping leads to the decline of mood states and further the sleep disorders [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, active coping was adversely associated with poor sleep quality, whereas negative coping was positively related to it. Similar results were also found in previous studies [ 17 , 33 ]. The underlying mechanism might be that passive coping leads to the decline of mood states and further the sleep disorders [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that personal factors (e.g., age, gender, marital status and lifestyle), environmental conditions, psychological diseases and other factors can influence individuals' sleep quality [15,16]. In recent years, there is increasing evidence that coping style might be an independent and important predictor of sleep quality [17][18][19][20]. Coping refers to stable cognitive and behavioral strategies adopted by individuals in response to external and internal challenges or stressors, which can be divided into two styles: active coping and passive coping [21].…”
Section: Introductionmentioning
confidence: 99%
“…Contrastingly, negative coping reflected the level of negative coping styles, e.g. drinking/smoking to forget about problems or relying on others to solve these problems [ 19 ]. The scale adopted a 4-point Likert scoring system.…”
Section: Methodsmentioning
confidence: 99%
“…Umiejętność ta wiązała się z lepszym snem, rzadszym występowanie senności dziennej oraz -co wydaje się najistotniejszelepszym funkcjonowaniem w ciągu dnia. Zauważono również, że osobom cierpiącym na bezsenność częściej zdarza się stosowanie niepożądanych metod radzenia sobie ze stresem; jako jedna z metod leczenia zalecana jest nauka prawidłowych wzorców i zastąpienie nimi złych nawyków [30,31]. W niniejszym badaniu oceniono jedynie "naturalne" zdolności radzenia sobie ze stresem.…”
Section: Ys K U Sj Aunclassified